Evaluation of Malaysia MOOCs development: from the student perspective - Ab Jalil, Habibah; Ismail, Alyani; Ab Aziz, Sidek; Atan, Hanafi; Alias, Abd Karim; Nordin, Norazah; Bakar, Norasiken; Alsagoff, Zaid Ali; Md. Saad, Mohd Nazri (Routledge, 2019)
A massive open online course (MOOC) is an example of an education evolvement as an online open course that is structured around a set of learning goals and facilitates the creation of learning community without restrictions. The aim of this chapter is to evaluate the effectiveness of deployment of four pilot MOOCs developed as part of the Malaysia MOOC initiative. Participants were first-year students in the first semester 2014/2015 from Malaysia HEI that registered for the four courses, Tamadun Islam dan Tamadun Asia (TITAS), Hubungan Etnik, Introduction to Entrepreneurship, and ICT Competency. Quantitative data was collected through a set of questionnaires filled out by a total of 4,449 first-year students. Collected data from the online survey were analyzed through descriptive analysis (frequency and mean). The results revealed that there are positive student insights on MOOCs’ curriculum, learning design, content quality, and impact on teaching and learning activities. However, the university spends less effort on the infrastructure, as the students depend only on the universities’ network connection. Hence, this initiative is promising, and MOOCs could potentially become “the” platform of teaching and learning in transforming education in the digital age.